Victimization of minors in online sexual abuse: a review of international studies - A.S. Medvedeva (Современная зарубежная психология)
Context and relevance. The problem of sexual exploitation of children and adolescents has become even more acute after the advent of the Internet and the increase in online activity of people. The attacks began to be carried out in virtual space, acquired a completely different form, which poses a challenge to specialists of various profiles. In addition to studying the mechanisms of criminal influence, it is important to pay attention to the cyber-victim behavior of children and adolescents, the motives for their participation in sexualized communication with unfamiliar online users and the ability to stop it, taking into account the most relevant data from foreign studies of the problem. Objective. To analyze the research conducted over the past five years on the victimization of children and adolescents in online sexual exploitation and to identify the factors that make minors vulnerable to harassment. Hypothesis. Individual reasons for children and adolescents engaging in sexualized online interactions with adults have a common core. Methods and materials. For the study, scientific publications by foreign authors on the topic of sexual exploitation of children and adolescents on the Internet, posted on the ResearchGate database over the past five years, were selected. Results. An analysis of publications allowed us to identify seven common factors that determine the vulnerability of minors to sexual exploitation. They are related to age, sex, gender, somatic, social characteristics, as well as manipulations by the criminals themselves. The identified factors are based on the psychological need of children and adolescents for productive interpersonal interaction, as well as the specificity of their psychosexual development, which determines their interest in the topic of sexual relationships between people. Conclusions. Prevention of children and adolescents' involvement in sexualized Internet communications should include informing them about cyber threats, developing an understanding that online and offline relationships are not equivalent, education on issues of sexual relationships between people, monitoring their psycho-emotional state and the success of socialization.